Major factors influencing the effectiveness of community-led total sanitation among communities in Kilifi and Marsabit Counties in Kenya - Omufwoko, Tobias M.; Odongo, Alfred O.; Karama, Mohamed (International Journal Of Community Medicine And Public Health, 2024)
Background: Poor sanitation contributes to about 775,000 deaths annually and is one of the world's most significant health and environmental challenges, especially in developing nations. This study examined factors influencing the effectiveness of CLTS as an approach to delivering open defecation-free communities in Kilifi and Marsabit Counties in Kenya. Methods: The study methodology included a comparative cross-sectional study of the two diverse study populations. The researchers recruited 811 participants after a multistage sampling procedure was used to sample the villages and the households. Quantitative data was analysed using SPSS tool version 26.0. Descriptive and inferential statistics and propensity score matching (PSM) were used to analyse the data. All tests were done at p≤0.05. Results: Open defecation dropped from 30% to 13.45% after CLTS interventions. There was a significant statistical association between household heads having a college-level education (A.O.R=10.273, p=0.013), being above 61 years (A.O.R=4.046, p=0.009), having a higher monthly income (A.O.R=6.461, p=0.091), and being female (A.O.R=1.792, p=0.03), and owning a sanitation facility. Also, households with heads with good handwashing and CLTS awareness (A.O.R=2.459, p=0.002) and (A.O.R=4.317, p=0.022) were statistically associated with owning sanitation facilities. PSM analysis found that CLTS programs impacted sanitation status, resulting in a 42% increase in facility ownership. Conclusions: The study established a statistical significance of CLTS and ownership of sanitation facilities in both counties. The results show that the CLTS program is effective and has positively impacted sanitation status by reducing open defecation levels in Kilifi and Marsabit.